Answer:
depending on what is happening then ye
Step-by-step explanation:
(12 * 7 + n)8=12.5
(12 * 7 + n)= 100
N= 16. The new number will be 16. Hope this helps. :)
Answer:
b. g(x) = ƒ(3x)
Step-by-step explanation:
We can use the graph to find the transformation which has been performed to obtain g.
g(x) is more stretched than x which means the function values are multiplied by some integer to obtain g(x). <u>This eliminates the options a and d.</u>
Now to check which factor is used to transform the function f(x) we can divide the x-coordinates of the points of new and old function.
So,
6/2 = 3
-6/-2 = 3
The function is stretched by a factor of 3.
Hence, the correct answer is:
b. g(x) = ƒ(3x) ..
The common factor is 7 so its
7(2x - 3)
H = 6 in
V=bh
H=v/b
H=36/6
H=6